2009
DOI: 10.4321/s1130-14732009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Purely intramedullary spinal cord primitive neuroectodermal tumor: case report and review of the literature

Abstract: Introduction. Primitive neuroectodermal tumors (PNETs) are malign neoplasms of the central nervous system which mainly locate in cerebellum (medulloblastoma). Primary intraspinal PNETs are rare. Within this group, we have found ten cases of purely intramedullary PNETs (IPNETs). In this report, we describe a new IPNET case and review the literature about these infrequent intramedullary tumors.Case report. A 17 month-old boy showed progressive decrease of motion in his lower extremities. Spine magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 436 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 436 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 86%
“…2 The prognosis and survival rate for patients with spinal cord Ewing sarcoma is not well known because of the rarity of the condition; however, based on previous cases (Table 1), the survival rate was 45% to 50% in primary cases and 30% to 35% in recurrent and metastatic cases. 436 In surviving cases, rehabilitation and physical therapy should be considered part of the treatment program to improve the patient’s neurological status. In the current case, the patient improved markedly after 4 months of physical therapy and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a series of 28 patients with peripheral PNET in their limbs showed a 1-year and 2-year survival rate of 100% and 64%, respectively 17 . In contrast, purely intramedullary PNET has dismal outcome: most patients die within two years in spite of surgical excision followed by radiotherapy and chemotherapy 18 . Whether extraosseous tumor origin may be a favorable prognosis factor is still unclear 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…These are small round cell tumors of neuroectodermal origin with high malignant potential (3). PNETs of the central nervous system (CNS) are uncommon malignant neoplasms of the cerebral hemispheres and suprasellar region and include supratentorial, infratentorial, brain stem, and spinal cord tumors (4). PNET usually occurs in children and only sporadically in adults (older than 20 years) (1) accounting for approximately 2.5% of brain tumors in children and 0.46% in adults (2).…”
Section: Introductionmentioning
confidence: 99%